HUMAN RIGHTS AND THE ENVIRONMENT (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The topic “Human Rights”, an ideal related to the dignified life of all people and nations, has as its scope intense reflection that considers aspects related to the right to the environment and its repercussion in people's lives. There are many challenges for Brazil, which seeks to match economic development with environmental protection, given the relevant biodiversity heritage in its territory, unparalleled with other countries. The study will look at Brazilian society with a specific focus on environmental protection, as a way of guaranteeing the fundamental right to a balanced environment. Two judgments will be analyzed: one delivered by the Inter-American Court of Human Rights, linked to the Organization of American States - OAS, and another delivered by the Superior Court of Justice. There will be brief comments on international commitments made by Brazil and then discussions on the apparent conflict between environmental protection as a guarantee for new generations and the urgent need for income generation in Brazil. In the end, we will propose ways from the action of the judiciary